Treatment of Discoid Lupus Erythematosus in a Dog with Human Intravenous Immunoglobulin - Choi, Yujin; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Lee, Dohee; Oh, Jimin; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Acta Scientiae Veterinariae, 2021)
Background: Discoid lupus erythematosus (DLE) is a common canine autoimmune skin disease, in which systemic manifestations are absent. Skin Lesions are usually present on the nasal planum, and characterised by erythema, depigmentation, erosion, ulceration, and crusting. The diagnosis is based on histopathological results, which should demonstrate lymphoplasmacytic lichenoid-interface dermatitis. Human intravenous immunoglobulin (hIVIg) has been used in veterinary medicine to treat cutaneous diseases including erythema multiforme, PF, and severe adverse cutaneous drug reactions. In human medicine, it has been effective to treat DLE. This report firstly describes the clinical response to hIVIg in a dog with DLE resistant to common immunosuppressive drugs. Case: A 5-year-old, intact female Shih Tzu presented with a 1-month history of slowly progressive black crusting on the nasal planum, chin, and claw. Based on the results of a dermatologic examination, superficial pyoderma was diagnosed. The skin lesions did not improve during and after anti-infective treatment. After removing the crusts, a skin biopsy was obtained from the muzzle. Histopathology of lesional skin biopsy specimens revealed lymphoplasmacytic interface dermatitis at the dermoepidermal junction. Microscopic examination also revealed vacuolar changes and pigmentary incontinence of the basal layer as a lichenoid tissue reaction. No mites or fungi were detected on the skin section. The absence of acantholytic cells excluded pemphigus foliaceus, which is also characterised by the lesions of the nasal planum. Based on the distribution of the lesions, histopathology and exclusion of other dermatoses, the dog was diagnosed with DLE. The skin lesions temporarily improved after treatment with prednisolone (2 mg/kg PO q12h). However, after tapering the dose of prednisolone, new black crusts developed on the nasal planum and claw. Although the dog was successively treated with other immunosuppressive drugs, including azathioprine, cyclosporin with dexamethasone, and mycophenolate mofetil, black crusts still remained. Due to the low efficacy of these immunosuppressive drugs, hIVIg was administered at 0.5 g/kg once daily for 4 days, for a total dose of 2 g/kg. During hIVIg administration, the crusted lesions gradually improved. After the hIVIg administration, the dog was treated with prednisolone (1 mg/kg PO q12h). The lesions were almost in complete remission at 21 days after an additional application of prednisolone. The skin lesions did not recur, and the treatment was eventually discontinued after 6 weeks of additional prednisolone application. Discussion: The standard treatment of canine DLE includes glucocorticoids, and second-line immunosuppressive drugs, such as azathioprine and cyclosporine, are usually added in cases resistant to steroids. This case suggests that hIVIg may be beneficial as an adjunctive treatment option for canine DLE, especially when the application of standard immunosuppressive drugs is limited due to adverse effects or low efficacy. There is evidence from several studies that the steroid-sparing effect of hIVIg is significant in human patients. In the current case, the effective dose of prednisolone was reduced to 2 mg/kg/day after hIVIg administration, and prednisolone therapy was finally discontinued completely. The hIVIg appears to lower the daily steroid dose requirement in this dog. Keywords: autoimmune skin disease, discoid lupus erythematosus, canine dermatology, immunosuppressive drug, human intravenous immunoglobulin.